Beyond workforce preparation: contested visions of 'twenty-first century' education reform. Issue 1 (2nd January 2019) - Chang, Ethan
ABSTRACT: Contrary to educational policy and research assumptions about an immanent 'twenty-first century' future, this article uses the concept of 'sociotechnical imaginaries' to trace how nonprofit actors in California invented and materialized distinctive visions of educational progress. Drawing on interview and ethnographic fieldnote data, I illustrate two contrasting sociotechnical visions: A Silicon Valley vision that aimed to reduce inequalities in test-based outcomes by disseminating 'achievement technologies'; and an Oakland vision that aspired to address systemic environmental, economic and educational inequities using 'civic technologies'. The diversity of these futures, and the distinctive kinds of digital technologies that co-produced these visions, trouble assumptions about 'technology' as an unquestioned good and problematize constructions of the 'twenty-first century' as an ostensibly shared, democratic future. I conclude by encouraging educational researchers to clarify a politics of the 'twenty-first century' and explore how 'bounded imaginaries', like those evident in the Oakland case, offer a potentially fruitful basis for reframing global education technology policies.